2017
DOI: 10.1016/j.cels.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

A Cell-Surface Membrane Protein Signature for Glioblastoma

Abstract: SUMMARY We present a systems strategy that facilitated the development of a molecular signature for glioblastoma (GBM), composed of 33 cell-surface transmembrane proteins. This molecular signature, GBMSig was developed through the integration of cell-surface proteomics and transcriptomics from patient tumors in the REMBRANDT (n=228) and TCGA datasets (n=547) and can separate GBM patients from controls with an MCC value of 0.87 in a lock-down-test. Functionally, 17/33 GBMSig proteins are associated with TGFβ si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 70 publications
1
33
0
Order By: Relevance
“…Studying proteins exposed on the surface of cells requires biochemical approaches that enrich for membrane proteins. Plasma membrane proteins on intact cells can be first biotinylated and then the isolated fraction subjected to mass spectrometry ( Ghosh et al, 2017 ; Shin et al, 2003 ). Membranes and all their constituents can be also extracted from lysed cells by means of a Percoll/sucrose density gradient ( Lund et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studying proteins exposed on the surface of cells requires biochemical approaches that enrich for membrane proteins. Plasma membrane proteins on intact cells can be first biotinylated and then the isolated fraction subjected to mass spectrometry ( Ghosh et al, 2017 ; Shin et al, 2003 ). Membranes and all their constituents can be also extracted from lysed cells by means of a Percoll/sucrose density gradient ( Lund et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Levels of tricarboxylic acid cycle enzymes such as isocitrate dehydrogenase and aldehyde dehydrogenase decrease in response to antiangiogenic therapy, suggesting the cells evade death by increasing glycolysis ( Demeure et al, 2016 ). Additionally, a systems-based statistical analysis of a proteomic and transcriptomic signature of GBM was identified, concluding a strong link between GBM invasive properties and the TGF- β signaling pathways ( Ghosh et al, 2017 ). Targeting these pathways may inhibit GBM proliferation; however, target validation is necessary to rule out proteins that do not drive tumor growth.…”
Section: Emerging Targets In Glioblastomamentioning
confidence: 99%
“…Proteogenomic profiling of GBM tissues showed high expression of CD44 [23] and recent GBM systematic analysis further supported CD44 as a GBM cell surface antigen [26].…”
Section: Identifying Existing Drugs Targeting Gbm Signature and Cd44 mentioning
confidence: 77%
“…CD44 is a transmembrane receptor and has multifaceted functions in both normal and disease physiology. OMICS studies have identified CD44 to be overexpressed in many types of cancer including glioblastoma [26,27]. Based on our analysis, CD44 seems particularly important as it can be both identified in transcriptomics and proteomics-based approaches, among the top hub gene and whose high expression correlate with poor disease-free survival.…”
Section: Co-expression Network Of Cd44mentioning
confidence: 80%